Tren Belanja Online: Analisis Pengaruh Online Customer Review dan Brand Image terhadap Purchase Intention di Shopee dengan Trust sebagai Mediasi - Adam Afifallah Maulidan Rizqi; Aflit Nuryulia Praswati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this research is to investigate in depth the causal relationship between online customer reviews and brand image on purchase intention of fashion products on the Shopee platform, with trust as an intervening variable. This study adopts a quantitative approach with a non-probabilistic sampling technique through a purposive sampling method, involving 170 participants selected based on specific criteria. The data collection instrument is a digital questionnaire that is distributed online. The data obtained is then processed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique with SmartPLS software. The findings show that both online customer reviews and brand image provide a positive and significant contribution to purchase intention. In addition, both variables also significantly strengthen trust, which then significantly influences purchase intention. Furthermore, trust plays an essential mediator in bridging the influence of online customer reviews and brand image on purchase intention.